Symmetry in Special and General Relativity - Tasson, Jay (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The development of special and general relativity has relied significantly on ideas of symmetry. Similarly, modern efforts to test these theories have often sought either violations or extensions of the symmetries seen, and symmetry is regularly used a tool in seeking new applications. In this Special Issue of symmetry, we explore some contemporary research related to symmetry in special and general relativity.